The Effect of Digital Literacy on Employee Performance at LLDIKTI Region X Padang - Salwa Humaira; Desriyeni Desriyeni (Darul Yasin Al Sys, 2026)
Although digital literacy has been widely examined in organizational and educational contexts, research specifically analyzing its effect on employee performance within the LLDIKTI environment remains relatively limited. This study aims to analyze the effect of digital literacy on employee performance at LLDIKTI Region X. A quantitative approach with a survey method was employed, involving 73 respondents selected through saturation sampling. Data were collected using a questionnaire and analyzed through simple linear regression with the assistance of SPSS software. The findings indicate that digital literacy has a positive and significant effect on employee performance at LLDIKTI Region X, as shown by a t-value of 5.911 and a significance level of p < .05. The coefficient of determination, R² = .330, indicates that digital literacy contributes 33% to employee performance, while the remaining variance is explained by other factors outside the model. These findings demonstrate that employees with stronger digital literacy tend to show better performance in carrying out work tasks within higher education service institutions. This study contributes to the literature on digital literacy and human resource performance by emphasizing the importance of digital competence in improving workplace effectiveness. The practical implication is that LLDIKTI Region X should continue strengthening employees’ digital competencies through systematic training, mentoring, and professional development programmes. Further research is recommended to examine additional organizational, technological, and individual factors that may influence employee performance.